2021
DOI: 10.1111/jrh.12635
|View full text |Cite
|
Sign up to set email alerts
|

Geographic, racial/ethnic, and socioeconomic inequities in broadband access

Abstract: Introduction Broadband access is a “super determinant of health.” Understanding the spatial distribution and predictors of access may help target government programs and telehealth applications. Our aim was to examine broadband access across geography and sociodemographic characteristics using American Community Survey (ACS) data. Methods We used 5‐year ACS estimates from 2014 to 2018 to evaluate broadband access across contiguous US census tracts. Rural‐Urban Commuting Area (RUCA) codes were categorized as me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 16 publications
4
25
0
Order By: Relevance
“…Similar international studies [41,42] have reported on broadband access challenges with telehealth programs for both rural and underserved populations. The shift to internet-based health consultations and associated increased reliance on internet connections because of the impact of the COVID-19 pandemic have further negatively affected telehealth use for those with existing health disparities.…”
Section: Trust In the Technology And Telehealth Systemsupporting
confidence: 63%
“…Similar international studies [41,42] have reported on broadband access challenges with telehealth programs for both rural and underserved populations. The shift to internet-based health consultations and associated increased reliance on internet connections because of the impact of the COVID-19 pandemic have further negatively affected telehealth use for those with existing health disparities.…”
Section: Trust In the Technology And Telehealth Systemsupporting
confidence: 63%
“…Existing health and technological disparities became more apparent during COVID-19 [101,102], and future studies are needed to better understand the relationship between the services offered and the needs and abilities of patients and providers. For example, the lack of access to adequate devices and Wi-Fi resources for VCVs is well documented [1,103,104], but the impact of other factors, such as language barriers and availability of privacy and safe spaces for VCVs [105], require better understanding and accommodation. Specifically in relationship to rapport, there is some evidence that qualitative differences between type of device, strength of broadband, and level of literacy impact the level and quality of empathetic communication within VCVs [92].…”
Section: Future Researchmentioning
confidence: 99%
“…In addition, increased availability of online interventions due to the SARS-CoV-2 pandemic may allow for penetration of evidence-based programs in rural areas. However, access to broadband internet and internet-capable devises still lags in many rural communities (49), which may ultimately limit the utility of online treatment options. These data also suggest that once methamphetamine became readily available in the area, use significantly increased (50).…”
Section: Discussionmentioning
confidence: 99%